Correlation between auto/mitophagic processes and magnetic resonance imaging activity in multiple sclerosis patients - Castellazzi, Massimiliano (J Neuroinflammation, 2019)
BACKGROUND: An alteration of autophagy and mitophagy, two highly conserved lysosome-dependent degradation pathways involved in the maintenance of cellular homeostasis, has been associated with multiple sclerosis (MS). OBJECTIVE: To search the level of autophagy-related 5 (ATG5) and Parkin proteins, as markers of autophagy and mitophagy respectively, and lactate in a cohort of MS patients. METHODS: Cerebrospinal fluid (CSF) and serum samples from 60 MS patients were analyzed: 30 with magnetic resonance imaging (MRI) evidence of disease activity, gadolinium (Gd)-based contrast agent positive (Gd+), and 30 without MRI evidence of disease activity (Gd−). ATG5, Parkin, and lactate were measured using commercially available products. RESULTS AND CONCLUSIONS: Serum levels of ATG5, Parkin, and lactate were more elevated in Gd+ than in Gd− MS patients (p < 0.0001), and CSF concentrations of ATG5 and Parkin were greater in Gd+ than in Gd− MS (p < 0.0001). Our results demonstrated that molecular markers of autophagy and mitophagy are increased in CSF of MS patients during the active phases of the disease and that these catabolic markers, together with lactate, are also remarkably augmented in blood suggesting a role of these processes in MS pathogenesis and the possible use of these molecules as biomarkers of disease activity.